Analisis Pelaksanaan Pencegahan Covid-19 di Rumah Sakit Umum Daerah Kabupaten Ogan Ilir - Ratnapia, Martha Dwi; Saptawan, Ardiyan; Berlian, Ong (@-Publik: Jurnal Administrasi Publik, 2022)
This study uses a qualitative approach, namely research that aims to describe certain circumstances, which are described in words or sentences. The data analysis technique used is qualitative data analysis techniques, while the data collection techniques used are observation, interviews and documentation. This study uses the theory of (Mazmani & Sabatier, 1983) to see the process of implementing the COVID-19 prevention measures. The results showed that the implementation of covid-19 prevention at the Regional General Hospital of Ogan Ilir Regency was not carried out properly according to the target set by the OI Hospital because there was no socialization regarding the Covid-19 handling policy and its operational guidelines and technical guidelines for medical personnel from the management of the Ogan Hospital. Ilir so that the appointment of the Covid-19 Handling Task Force at the Ogan Ilir Hospital was not in accordance with the guidelines for handling COVID-19 itself. The problem of the lack of security for medical personnel as the front line in handling Covid-19 is the result of the lack of availability of personal protective equipment (PPE), the lack of clarity in the protection from the RSUD for medical personnel and the unavailability of a halfway house for medical personnel who treat corona patients and the lack of optimal policies implemented. at the Regional General Hospital of Ogan Ilir Regency regarding the prevention of covid-19, causing people to not understand the steps for personal hygiene, implementing clean and healthy living, the importance of protecting the environment and implementing correct health protocols.